Photoluminescence lifetime in porous silicon - Adwan N. H. Al-Ajili (Tikrit Journal of Pure Science, 2023)
Lifetime of photoluminescence emitted by porous silicon has been investigated by using pulsed nitrogen laser as excitation source. This research also involved sample preparation. This in itself necessitated software and hardware development to enable interfacing and data logging using PC.